THE IMPACT OF BURNOUT SYNDROME IN MEDICINE: A MENTAL HEALTH REVIEW - Pedro do Valle Varela, João; Silva Santa Clara, Nicolly; Vitor Amorim Barbosa, João; Giselle Batt, Jennifer; Fairana Godeline Essali, Genese; Picinini Freitas, Lucas; Vergílio Lugão de Azevedo, Pedro; Latini Azevedo, Juliana; Lobato Ferreira, Juliana; Luiz Teixeira Fully, Fabio (Health and Society, 2024)
Burnout syndrome is an increasingly prevalent mental health problem in medicine, characterized by physical, emotional and mental exhaustion caused by excessive and stressful work. This study aims to review the impact of burnout syndrome in medicine, highlighting its causes, symptoms and consequences for the health of professionals. This study aims to analyze the impact of burnout syndrome on the mental health of medical professionals, identifying its main causes, symptoms and consequences. In addition, it seeks to present strategies for preventing and managing this syndrome, with a view to promoting the health and well-being of doctors, highlighting the importance of the mental health of health professionals and discussing measures to promote a healthier and more balanced working environment. This is a bibliographical review, using qualitative premises, with the PubMed, Scopus, Web of Science and Scielo databases. To better refine the research, the health descriptors “Burnout Syndrome”, “Health Professionals”, “Occupational Stress” and “Mental Health” were used. Burnout syndrome in medicine can be triggered by various factors, including excessive workload, lack of emotional support, pressure for results and long working hours. Symptoms include emotional exhaustion, depersonalization and decreased professional fulfillment. The impact of burnout syndrome in medicine is significant, affecting not only the mental health of professionals, but also the quality of care provided to patients. Doctors with burnout are more likely to make medical mistakes, suffer from physical and mental health problems and have lower job satisfaction. Therefore, in order to prevent and manage burnout syndrome, it is important for medical professionals to adopt self-care strategies, such as practicing regular physical activity, setting healthy work limits and seeking emotional support when necessary. In addition, health institutions should promote an organizational culture that values the well-being of professionals and offers adequate support to prevent and treat burnout syndrome. It can therefore be concluded that burnout syndrome is a serious problem in medicine, with significant impacts on the health and well-being of professionals. It is essential that doctors are aware of the signs of this syndrome and adopt measures to prevent and manage its effects. In addition, healthcare institutions should implement policies and practices that promote a healthy and supportive work environment for their professionals.